Investigation of the relationship between Cobb angle and inflammatory markers in patients with adolescent idiopathic scoliosis (Annals of Medical Research, 2024)
Aim: The role of inflammation and immune system pathologies in Adolescent Idiopathic Scoliosis (AIS) has recently been the focus of research. It has been reported that the neutrophil/lymphocyte (NLR), platelet/lymphocyte (PLR) and monocyte/lymphocyte (MLR) ratios may be markers of inflammation severity. In addition, the systemic immune inflammation index (SII), including peripheral neutrophils, lymphocytes, monocytes and platelets, systemic inflammatory response index (SIRI) and systemic inflammation total index (AISI) are also known as inflammation marker indexes. This study aimed to investigate the relationship between NLR, PLR, MLR, SII, SIRI, AISI and Cobb angle in patients with AIS.Materials and Methods: Pediatric patients aged 10-18 years who were requested to undergo scoliosis radiography with a preliminary diagnosis of AIS were retrospectively screened. Cobb angles, neutrophils, lymphocytes, platelets, monocytes, neutrophil percentage, white blood cells (WBC) and hemoglobin values ​​were recorded. The NLR, PLR, MLR, SII, SIRI and AISI values ​​were calculated. The patients were divided into four groups according to their Cobb angle. We examined whether there was a difference between the groups in terms of neutrophil, lymphocyte, platelet, monocyte, neutrophil percentage, WBC, Hemoglobin, NLR, PLR, MLR, SII, SIRI, AISI values. It was examined whether there was a correlation between the Cobb angle and NLR, PLR, MLR, SII, SIRI and AISI in patients diagnosed with scoliosis with a Cobb angle greater than 10°.Results: A significant difference in NLR was observed between groups 2 and 4. A positive correlation was observed between groups 2, 3, and 4 patients with a Cobb angle greater than 0 and NLR; no correlation was observed between PLR, MLR, SII, SIRI and AISI.Conclusion: NLR, which is associated with the severity of inflammation, is a marker that correlates with the scoliosis angle in patients with AIS. Larger-scale studies are needed to elucidate the relationship between AIS and the NLR.
Keywords: Adolescent idiopathic scoliosis; N/lymphocyte (NLR); Platelet/lymphocyte (PLR); Systemic immune inflammation index (SII); Systemic inflammatory response index (SIRI); Systemic inflammation total index (AISI)